The neighbours of the European Union's neighbours diplomatic and geopolitical dimensions beyond the European neighbourhood policy - Gstohl, Sieglinde; Lannon, Erwan (Ashgate Pub., 2014)
Should the European Neighbourhood Policy stop at the borders of the European Union's immediate neighbouring countries? This book is the first full length study of the 'neighbours of the EU's neighbours', a concept originally introduced by the European Commission with reference to Saharan Africa, the Middle East and Central Asia.